Exploring the Use of Cluster Analysis in Market Segmentation for Targeted Advertising - Nur, Muhammad Farras; Siregar, Amora (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
In the rapidly evolving field of digital marketing, precise targeting and segmentation have become essential for optimizing advertising efforts, yet traditional methods often struggle to adequately address the dynamic nature of consumer behaviors. This study delves into the efficacy of cluster analysis as a robust tool in market segmentation, particularly aimed at enhancing the precision of targeted advertising campaigns. By employing a case study approach, the research meticulously analyzes real-world advertising campaigns across various industries, utilizing cluster analysis to segment the market and employing qualitative data analysis to evaluate the outcomes in terms of engagement and conversion improvements. The results indicate that cluster analysis not only facilitates a deeper understanding of market segments but also leads to more tailored and effective advertising strategies. Companies implementing this method reported significant improvements in campaign performance, with higher engagement and conversion rates compared to traditional segmentation approaches. This study underscores the advantages of employing advanced statistical methods like cluster analysis in market segmentation, highlighting its potential to transform targeted advertising by enabling advertisers to adapt more swiftly and effectively to market dynamics. The implications for practice suggest that businesses should integrate cluster analysis into their marketing strategies to gain a competitive edge through enhanced customer insights and optimized advertising effectiveness, thereby contributing valuable empirical evidence to the existing literature.